Effective Use of BV-AVD Regimen in The Management of Classical Hodgkin Lymphoma: A Case-Based Approach - Sasikumar, Shirly; Anandan, Mathesh; Alan, Darius; Kothandan, Dhivya (Indian Journal of Pharmacy Practice)
Classical Hodgkin Lymphoma (CHL) is a malignant lymphoproliferative disorder characterized by the presence of Reed-Sternberg cells(R-SC), which are large, multinucleated cells within an inflammatory microenvironment of immune cells, fibrosis, and necrosis. While its exact cause remains unclear, CHL is strongly associated with Epstein-Barr Virus (EBV) infection, genetic factors, and immune dysregulation. Common symptoms include fever, night sweats, unexplained weight loss, pruritus, fatigue, and hepatosplenomegaly. This report presents a rare case of CHL of mixed cellularity in a 35-year-old pregnant woman, who was admitted with generalized pruritus, joint pain, and bilateral upper lymphadenopathy. The diagnosis was confirmed through a PET-CT scan, bone marrow biopsy, and lymph node excision biopsy. The patient was initiated on cycle 1B chemotherapy with adriamycin, vinblastine, dacarbazine, and Brentuximab Vedotin (BV-AVD), along with supportive care and lifestyle modifications to ensure optimal maternal and fetal outcomes.
Keywords: Hodgkin lymphoma; PET-CT; BV-AVD regimen; Supportive Care